Pravno-kultne strukture v prostoru Altenerdinga na Bavarskem Juridical-Cult Structures in the Region of Altenerding in Bavaria - Pleterski, Andrej (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article presents the juridical-cult structures that existed at the Bavarian cemetery of Altenerding near Munich during the second half of the 5th century and the first half of the 6th century. The direction of the sunset and sunrise during the solstices set the main course of orientation at the cemetery. The ritual angle of natural equilibrium was also set by this course. The central cult and juridical locality of the former Westergau was also at this cemetery. Old Gallic-Roman measuring units were applied to aid in the process of organization of space. Furthermore, the influence of Pythagorean symbolism is also evident.